Switchable single- and dual-wavelength erbium-doped fiber laser assisted by four-wave mixing with wide and continuous tunability - Cholan, Noran; Al-Mansoori, Mohammed Hayder; Muhammad Noor, Ahmad Shukri; Ismail, Alyani; Mahdi, Mohd Adzir (Springer Berlin Heidelberg, 2014)
A widely tunable and stable erbium-doped fiber laser based on four-wave mixing effect in a highly nonlinear fiber is proposed and experimentally demonstrated. By adjusting reflected power from a dual-selective element, the ring laser is switchable between single- and dual-wavelength operations. The tuning range of the single laser is 22.78 nm, from 1,542.07 to 1,564.85 nm, while the wavelength spacing of the dual-wavelength can be continuously tuned from 0.52 to 22.78 nm. The laser is stable with output peak power fluctuation of <1 dB in 30-min interval.